Employee Performance is Influenced by Training Through the Career Development of PT. Mila & Juniors - Sanusi Silitonga, Eddy (Green Publisher, 2023)
The purpose of this study was to analyze and determine the positive and significant effect of training on employee performance through career development as an intervening variable at PT. Mila & Juniors. The subjects in this study were all employees of PT. Mila & Juniors using a quantitative approach method. Meanwhile, to analyze the pattern of relationships between variables in this study using path analysis with the aim of knowing the direct or indirect effect of a set of independent variables on the dependent variable. The results of this study state that there is a direct influence between training on employee performance at PT. Mila & Juniors without going through Career Development.